KESADARAN HUKUM DI LINGKUNGAN PERUMAHAN KEC.SETU KAB.BEKASI: Indonesia - Wasito, Wasito; Fitryantica, Agnes; Wildan, Nandana; Akbar, Chairil; Sya'ban, Imam Ali; Kurniawan, Kurniawan; Randut, Krispianus; Saehudin, Saehudin; Kohar, Kohar; Dewi Fortuna, Miranda; Novitasari, Rohma (CV. Era Digital Nusantara, 2024)
Law students and students at IBLAM Jakarta College of Law, Carrying out Real Work Lecture Activities or KKN as a form of community service. Implementation of Internship Activities in RW .014 Ciledug Village, District. Setu, Kab. Bekasi, West Java on Tuesday 23 April 2024. In this area, society has experienced very rapid development, resulting in a shift in urban functions to suburban areas. The next consequence is that suburban areas will experience a process of spatial transformation in the form of residential densification and social transformation. economy as a further impact of social transformation. We convey this Legal Awareness in Residential Environments with the aim of ordering and securing streets in residential environments so as not to disturb fellow road users, following government regulations based on Law Number 38 of 2004 concerning roads and the LLAJ Law, namely DKI Jakarta Regional Regulation 8/2007 concerning regulations making speed bumps and to provide driving comfort for road users